Prevalence of Metabolic Syndrome and Its Association with Sociodemographic Characteristics in Participants of a Public Chronic Disease Control Program in Medellin, Colombia, in 2018 - Higuita-Gutiérrez LF (Dove Medical Press, 2020)
Luis Felipe Higuita-Gutiérrez,1 Wilson de Jesús Martínez Quiroz,2 Jaiberth Antonio Cardona-Arias3 1Cooperative University of Colombia, University of Antioquia, Medellín, Colombia; 2Metrosalud, Medellín, Colombia; 3School of Microbiology, University of Antioquia, Medellín, ColombiaCorrespondence: Luis Felipe Higuita-Gutiérrez Calle 70 Número 52 – 51, Medellín, ColombiaTel +5742198486Fax +5742195486Email luis.higuita@campusucc.edu.coBackground: Metabolic syndrome has increased to epidemic levels in low- and middle-income countries. The knowledge on metabolic syndrome and its related diseases constitutes a clinical, epidemiological, and economic challenge of great relevance. The frequency of metabolic syndrome may vary between populations depending on age, sex, lifestyle, and culture; however, in Colombia, there is only little research, and the available studies focus on small populations that do not allow estimating their prevalence and distribution in different sociodemographic groups. We aimed to estimate the prevalence of metabolic syndrome and its association with sociodemographic characteristics in participants attending public chronic disease control programs in Medellin, Colombia, in the year 2018.Methods: We conducted a cross-sectional study in all patients who participated in a public chronic disease control program. Involved in this study were 68,288 individuals who attended at 10 hospital units and were strategically distributed in the city. The diagnostic criteria of the metabolic syndrome and its components were based on the consensus of the Latin American Diabetes Association. The data on age, sex, blood pressure, weight, height, physical activity, medications, lipid profile, and glycemic and glycosylated hemoglobin levels were obtained for clinical records. The prevalence, Pearson’s chi-square test, prevalence ratios (Kato-Katz method), and odds ratios (Woolf method) were estimated with 95% confidence intervals. A multivariate adjustment model was used with a logistic regression model to identify potential confounders using Epidat 4.2 and SPSS® 25.0.Results: The prevalence of the syndrome was 35.4%, with abdominal obesity in 82.3% individuals, hypertension in 48.6%, glucose intolerance in 25.5%, and hypertriglyceridemia in 22%. The prevalence of the syndrome exhibited statistical differences according to the area of residence. It was 15% higher in women; 31% and 59% higher in young and older adults, respectively, than in individuals aged < 25 years; 11% and 13% higher in the illiterate population and population with primary studies than in individuals with higher education; and approximately 200 times higher than those who are sedentary.Conclusion: A high prevalence of the syndrome and its constitutive factors in the study population demonstrated the importance of controlling it and increasing community-based prevention strategies, prioritizing the identified groups that are at the highest risk.Keywords: prevalence, metabolic syndrome, risk factor, Colombia